Analisis Strategi Pemasaran dengan Menggunakan Metode Business Model Canvas untuk Meningkatkan Volume Penjualan pada PT Allianz Life Indonesia Cabang Surabaya - Rayna Shafiyah Salsabila Haris; Jojok Dwiridotjahjono (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The insurance industry is one of the industries with products that are needed by everyone but with a fairly low market penetration, this is due to a lack of financial education. In this study, researchers used PT Allianz Life Indonesia Surabaya Branch as the object of research. The purpose of this study is to find out and analyze the marketing strategy or business system used by PT Allianz Life Indonesia Surabaya Branch. The research method used is descriptive with a descriptive approach, data collection techniques are interviews and observations related to the existing marketing strategy at PT Allianz Life Indonesia Surabaya branch, the data is analyzed using BMC (Business Model Canvas). The respondents in this study consisted of the Head of Agency Development and the chairman of AAJI for the East Java Region, Business Partners of Allianz, and customers from Allianz who were selected purposively with a total of 5 people. The results show that Allianz's marketing strategy since 2014 has changed to a business system from the previous branch system, agency system and currently using the